The potential of collective power in a Global Production Network: UNICOME and Metro Cash & Carry in India - Franz, Martin (ERDKUNDE, 2010)
The transnational expansion of large retailers like Metro and Wal-Mart and its consequent power shifts have caused trade unions in the company’s host countries of their expansion to react differently. These reactions include the development of international union networks, the organisation of employees in the new supermarkets and resistance against new competitors of old-established retailers. Unions are part of the extra-firm networks of global production networks and influence their development and spatiality. However, to develop collective power in a global production network, unions have to develop strategies that are able to overcome the spatial asymmetry between the transnationally organised companies and the place-bound labour. This paper analyses the strategies of the Indian union UNICOME (the Union for Commerce Employees in India) to develop collective power in a Global Production Network in the retail sector, namely the transnational retailer and wholesaler Metro. The case study shows how a union’s greater power in the company’s German home market was harnessed in order to develop collective power in India by means of network relationships.